The Alkali Tolerance of Broomcorn Millet (Panicum miliaceum L.) at the Germination and Seedling Stage: The Case of 296 Broomcorn Millet Genotypes - Ma, Qian; Wu, Caoyang; Liang, Shihan; Yuan, Yuhao; Liu, Chunjuan; Liu, Jiajia; Feng, Baili (Frontiers in Plant Science, 2021)
Broomcorn millet (BM), one of the earliest domesticated cereal crops originating in northern China, can tolerate extreme conditions, such as drought and high temperatures, that are prevalent in saline-alkali, arid, and barren landscapes. However, its adaptive mechanism to alkali stress is yet to be understood. In this study, 80 mM and 40 mM standard alkali stress concentrations were used to respectively evaluate the alkali tolerance at the germination and seedling stages of 296 BM core collections. Principal component analysis, Pearson's correlation analysis, and F-value comprehensive analysis were performed on the germination parameters (germination potential, germination index, germination rate, vigor index, root length/weight, sprout length/weight, and alkali damage rate). Based on their respective F-values, the BM genotypes were divided into five categories ranging from highly alkali resistant to alkali sensitive. To study the response of seedlings to alkaline stress, we investigated the phenotypic parameters (plant height, green leaf area, biomass, and root structure) of 111 genotypes from the above five categories. Combining the parameters of alkali tolerance at the germination and seedling stages, these 111 genotypes were further subdivided into three groups with different alkali tolerances. Variations in physiological responses of the different alkali-tolerant genotypes were further investigated for antioxidant enzyme activity, soluble substances, malondialdehyde (MDA) content, electrolyte leakage rate, and leaf structure. Compared with alkali-sensitive genotypes, alkali-tolerant genotypes had higher antioxidant enzyme activity, soluble osmolyte content, and lower MDA content and electrolyte leakage rate, and more complete stomata structure. Taken together, this study provides a comprehensive and reliable method for evaluating alkali-tolerance and will contribute to the improvement and restoration of saline-alkaline soils by BM.